COMPUTATIONAL SOLUTIONS FOR DETERMINING THE SPATIAL-TEMPORAL EVOLUTION OF POLLUTANTS ON THE PRUT RIVER SECTOR IN GIURGIULEȘTI LOCALITY - GALINA MARUSIC; NINA SAVA; RODICA BRANIȘTE; VIOREL CĂRBUNE; VICTOR ABABII (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This work represents a research in the field of modeling the spatial-temporal evolution of pollutants. The Navier-Stokes equations were applied for the mathematical formulation of the spatial-temporal evolution of pollutants in river ecosystems, which are fundamental in fluid mechanics and describe the motion of fluids under different conditions. The SMS (Surface-water Modeling System) environment was used to determine the spatial-temporal evolution of pollutants, which is a software developed for modeling and simulation of surface water flows. An important evolution was the use of the application of 2/3D hydrodynamic models that simulate water flow in one plane, taking into account two spatial dimensions (longitude and latitude). The pollutant behavior simulation approach will contribute to the assessment and forecasting of potential natural catastrophes of riverine aquatic ecosystems. This research aims to explore the computational methods and technologies and comes up with some solutions that can be used to analyze the distribution and evolution of pollutants on the Prut river sector in Giurgiulești locality. A comparative analysis of several commercial Software (ANSYS Fluent, COMSOL Multiphysics, STAR-CCM+) and Open-Source Software (OpenFOAM, SU2, Gerris) was carried out, and the advantages of each software in the process of numerical simulation of the spatial-temporal evolution of pollutants were found.